Nanocomposites of Polymers and Inorganic Nanoparticles - Caseri, Walter Remo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue deals with the fascinating material class of nanocomposites consisting of extremely small particles (nanoparticles) which are embedded in polymers. Such materials are of paramount interest in various disciplines, especially chemistry, physics, biomedicine and materials science. Due to the diversity of the components of nanocomposites, they provide a broad spectrum of material properties and applications. The versatility of nanocomposites is indeed reflected by the research covered in this Special Issue. The field of nanocomposites includes innovative science and a source of inspiration for currently relevant economic topics as well as for envisaged technologies of the future. Indeed, this volume alludes to strategies for the preparation of nanocomposites and possibilities for a variety of applications, such as catalytic reactions, gas barriers, high refractive index materials, corrosion protection, electromagnetic inference (EMI) shielding, lithium ion batteries, tissue engineering and plastic surgery.